Assessing water quality from borehole sources in five communities of Ekpeyeland in Nigeria - Okidhika, Clinton Umebhidhi; Ekpete, Ozioma Adaunwo; Edori, Onisogen Simeon (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2024)
Corrosiveness and scaling a characteristics that are common to groundwater and are associated with the nature of underlying rocks and soils that the groundwater mixes up with. Drinking water quality is to a very large extent greatly determined by the corrosion and scaling of residential plumbing networks and rural community water schemes. This research was carried out to examine the corrosiveness and scaling tendency of groundwater in Ekpeye Kingdom, Rivers State, Nigeria. Water samples were collected from five communities in Ekpeyeland and were analysed for some physicochemical parameters using the American Public Health Association (APHA) standard operating procedures. The corrosiveness tendency and scaling potentials of the test water samples were measured using water stability indices that are computed from the studied physicochemical parameters like pH, temperature, TDS, EC, Ca2+, Mg2+, Cl- SO42-, HCO3- alkalinity and total hardness. The results revealed that 41.67 percent of the physicochemical parameters exceeded the permissible limit of the World Health Organization. These parameters are pH, temperature, total hardness, Ca2+ and Mg2+. The calculated values for the indices are LSI (-2.79 to -4.03), CSMR (3.32 - 13.91), RI (0.54 - 0.19), L-SI (0.50 - 0.20), PSI (8.49 - 9.66), RSI (10.88 - 11.88), AI (0.26 - 1.59). The result of the stability indices revealed that the test water samples of Ekpeyeland had significant scaling and corrosion potential. Liming, water softeners, filter beds and corrosion inhibitors are recommended to reduce the corrosion potential as well as lowering the scaling potential of drinking water.